PERAN PARTISIPASI PUBLIK DALAM PENYUSUNAN PROGRAM PEMBENTUKAN PERATURAN DAERAH DI KOTA BANDAR LAMPUNG - Sakung Wibowo; Okta Anita; Lintje Anna Marpaung (INTELIGENSIA MEDIA, 2025)
The Regional Regulation Formation Program is one of the programs that requires and must involve the participation of the role of the community as constituents in state life, considering that Indonesia is a democratic country where the highest decision is in the hands of the people, so the suggestions, considerations, and criticisms provided by the community are determining factors so that policies can be made by adjusting objective conditions and can be implemented well. The problem in this study is How is the mechanism of the role of community participation in program preparation, the preparation of regional regulations in Bandar Lampung City and What are the inhibiting factors of the mechanism of the role of community participation in the preparation of regional regulation programs in Bandar Lampung City. The research method used is a normative juridical method system in which this research is carried out by reviewing various sources such as journals and applicable legislation and an empirical approach that is carried out by looking at the reality in the field, in the form of interviews to be applied in order to answer questions related to research problems. The results of this study are: How is the mechanism of the role of community participation in the preparation of programs, the preparation of regional regulations in Bandar Lampung City and What are the inhibiting factors of the mechanism of the role of community participation in the preparation of regional regulation programs in Bandar Lampung City with the role of the Community vii SAKUNG WIBOWO has been running according to the rules but has not been optimal because there are still obstacles related to the preparation of the regional program. The DPRD in terms of the formation of the Regional Regulation will hold a Draft Regional Regulation to ask for input and suggestions from community stakeholders so that the regulation is ratified and implemented properly. and also several inhibiting factors are the community's unwillingness in the Regional Regulation Formation Program in Bandar Lampung City so that it becomes a serious problem for the Bandar Lampung City Government to socialize that this Prompeperda was made for the rules of community sustainability as well.